Surgical treatment of displaced acetabular fractures: report of 13 clinical cases - Pompili, M.; Verdano, M.A.; Marenghi, et al., L. (Acta Biomedica Atenei Parmensis, 2012)
Background and aim of the work: Displaced acetabular fractures are complex lesions which may cause severe consequences if not appropriately treated. The results are linked to the quality of the articular reduction. Anatomical reduction, through surgical treatment with rigid internal fixation, should be considered to obtain an early mobilization, reduce long term osteoarthritis evolution and make the acetabular cavity suitable to eventually recive a total hip prosthesis. The aim of this study is to evaluate functional and radiographic outcome of patients with displaced acetabular fractures surgically treated. Methods: Between 2005 and 2011, 29 displaced acetabular fracures were treated with open reduction and internal fixation. This study highlight our results in 13 patients with a mean follow-up of 29,5 months (range 5,5-66,3). Clinical evaluation was done according to the Harris hip score, while the radiological criteria were those of Kellgren-Lawrence. The associated injuries and complications were evaluated. Results: At the latest follow-up the radiological results, based on the Kellgren-Lawrence grading scale, showed 3 patients with a I grade of osteoarthritis, 5 with a II grade, 3 with a III grade and 2 with a IV grade. The average Harris hip score was 77 (range 37-100). Postoperative complications included avascular necrosis of the femoral head in 3 patients and heterotopic ossification in 2 patients. Conclusions: This study confirm that open reduction and internal fixation in displaced acetabular fractures represents the best treatment able to lead to a satisfactory functional outcome. Moreover, it posticipates long-term arthrosis and eventually makes easier the implant of total hip prosthesis